Pantang Larang Amongst Pontianak Malays and It's Relationship With Islamic Values - Dewi Ismu Purwaningsih (Khatulistiwa, 2020)
Pantang larang (superstition) is the belief in a society about the cause and consequence of people’s behavior considered supernatural or irrational. Pantang larang is widely spread from the parents to their children in a long time which has the important message about the life. It was descriptive qualitative research. Using ethnography of communication approach. The tool of collecting data in this research was questionnaire with field note and recording data. Collecting data used interview method to the 10 Malays. The data collected was analyzed to describe the meanings of pantang larang. In presenting the result, it was used informal method. The result showed that they are 22 pantang larang which literal meaning was the consequence happening if Malays breaking the rule and figurative meaning was the good message applicable in daily life. It also was found three Islamic values from pantang larang in Pontianak Malays. They are building the relationship between man and Allah, building relationship amongst human, and treating oneself properly